Seven golden rings : a tale of music and math - LaRocca, Rajani (Lee & Low Books Inc., 2020)
In ancient India, a boy named Bhagat travels to the rajah's city, hoping to ensure his family's prosperity by winning a place at court as a singer. Includes author's note about binary numbers.